2002
DOI: 10.4049/jimmunol.169.7.3963
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Actions of Prostaglandin E2 on Allergic Airway Responses in the Rat

Abstract: PGE2 has been reported to inhibit allergen-induced airway responses in sensitized human subjects. The aim of this study was to investigate the mechanism of anti-inflammatory actions of PGE2 in an animal model of allergic asthma. BN rats were sensitized to OVA using Bordetella pertussis as an adjuvant. One week later, an aerosol of OVA was administered. After a further week, animals were anesthetized with urethan, intubated, and subjected to measurements of pulmonary resistance (RL) for a period of 8 h after OV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 38 publications
(42 reference statements)
0
64
0
Order By: Relevance
“…In contrast, it displays beneficial actions in the lung in limiting inflammatory response and promoting tissue repair (2,34,42). Also, PGE 2 is a potent anti-inflammatory and immunoregulatory agent in allergic airway responses (43). Along these lines, recent findings demonstrated that both PGE 2 and/or PGD 2 switch eicosanoid biosynthesis from predominantly "proinflammatory" LTB 4 to "antiinflammatory" LXA 4 production that stops PMN infiltration in the murine air pouch (7).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it displays beneficial actions in the lung in limiting inflammatory response and promoting tissue repair (2,34,42). Also, PGE 2 is a potent anti-inflammatory and immunoregulatory agent in allergic airway responses (43). Along these lines, recent findings demonstrated that both PGE 2 and/or PGD 2 switch eicosanoid biosynthesis from predominantly "proinflammatory" LTB 4 to "antiinflammatory" LXA 4 production that stops PMN infiltration in the murine air pouch (7).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that cysLTs might suppress PGE 2 production through cysLT receptor signal. The overall action of PGE 2 in vivo (23,24) and in vitro (20 -22) seems to be immunosuppressive. In the present study Ind treatment before Prl treatment in vivo significantly decreased PGE 2 production in the lung and ameliorated the allergic immune responses, including CD4 ϩ T cell and DC activation, that had been potently suppressed by LTRA treatment (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 was found to exert bronchoprotective effects in patients with asthma [14]. In rats, the ovalbumin-induced early and late phase airway responses were inhibited by intratracheally administered PGE 2 [15].…”
Section: Introductionmentioning
confidence: 98%
“…PGE 2 was found to exert bronchoprotective effects in patients with asthma [14]. In rats, the ovalbumin-induced early and late phase airway responses were inhibited by intratracheally administered PGE 2 [15]. The activity of PGE 2 is mediated by four subtypes of E-type prostanoid receptors (EP), EP1, EP2, EP3, and EP4 [16].…”
mentioning
confidence: 99%